Analysis of Mental Health’s Awareness Effect and Physical Activity Towards Academic Perfromance Students - Isna Nurhaliza; Hermawa Pamot Raharjo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Academic success depends on several psychological and behavior related factors, like knowing how to take care of mental health and staying active with physical exercise. This study aims to examine the association between mental health knowledge, physical activity, and the academic performance of students at Universitas Negeri Semarang. This research uses a quantitative method and is based on a cross-sectional survey. A total of 200 students were selected using a purposive sampling approach. Mental health awareness was checked using a changed version of Mental Health Literacy Scale (MHLS), and physical activity was measured with the International Physical Activity Questionnaire-Short Form (IPAQ-SF). The students’ Grade Point Average was used to evaluate how well they did in their studies. The data was analyzed using multiple linear regression with IBM Statistic 25 Software. The study showed that mental health awareness was significantly associated with academic performance (p= 0.025). however, the adjusted coefficient of determination of 0.036 shows that these two variables explain only 3.6% of the variation in academic achievement. These findings indicate that mental health awareness was significantly associated with academic performance, whereas physical activity was not significantly associated with the GPAs of UNNES students, nevertheless, the contribution of the regression model to explaining student’ academic performance was relatively small.